Timing analysis of an active replication scheme for the road side units of vehicular networks - Almeida, João
This paper presents a timing analysis of an active replication scheme previously developed for the road-side units (RSUs) of infrastructure-based vehicular networks. This repli- cation strategy aims to increase fault-tolerance and reliability of RSUs, which are the master nodes of real-time vehicular communications protocols, e.g. V-FTT. Nevertheless, the proposed solution is protocol independent and can be applied to other wireless communications domains. The obtained results show that this replication scheme introduces low delay in the recovery procedure of failed RSU nodes and a small overhead in the protocol communications. However, under specific circumstances it can allow nodes non-compliant with the deterministic protocol to interfere with the scheduled packet transmission. In order to avoid this, some alternative solutions are briefly discussed at the end of the paper.